Collective Capability in Urban Community Empowerment: Analysis of Kelompok Usaha Bersama in Yogyakarta City - Pratiyudha, Pinurba Parama; Kafaa, Kafa Abdallah; Farransahat, Matahari; Suyatna, Hempri (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2022)
Community empowerment in the urban context has become a public discourse in the urban development perspective. Participation, inclusiveness, and collaboration encourage community empowerment in achieving equal urban welfare. This paper focuses on Kelompok Usaha Bersama or Joint Business Group (KUBE) community empowerment program, an initiative of the central government in collaboration with local stakeholders. The implementation of the KUBE program, which was specifically assigned, was examined in the Yogyakarta city area. By using the collective capability approach as a research lens, two findings were raised. First, the implementation of KUBE in Yogyakarta is an illustration of community empowerment policies in translating collective capabilities. Second, in realizing collective capability, an agency is required in the form of collective awareness and strong leadership.